Insights into Effective Corporate Financial Management Practices and Their Implications - Permata, Indah (Advances in Management & Financial Reporting, 2023)
Purpose: This study examines corporate financial management practices to identify key themes, patterns, and theoretical perspectives. The research aims to comprehensively understand financial planning, capital structure decisions, risk management, and financial reporting, highlighting their integration in optimizing financial resources and ensuring long-term sustainability. Research Design and Methodology: Utilizing a qualitative literature review approach, the study employs systematic literature search strategies combined with thematic and content analysis to synthesize findings from existing research. The study critically evaluates scholarly contributions to corporate financial management, governance, and regulatory frameworks, offering a structured understanding of best practices. Findings and Discussion: The research highlights the significance of a cohesive financial management framework that integrates strategic planning, risk mitigation, and financial transparency. Findings emphasize the role of corporate governance in fostering accountability and ethical financial decision-making. Additionally, continuous adaptation to market dynamics and regulatory changes is essential for effective financial management. Implications: The study contributes to the theoretical foundation of corporate financial management while offering practical insights for organizations to enhance financial performance and stakeholder trust. It recommends further research on emerging financial strategies, the influence of digital transformation on financial management, and the effectiveness of governance mechanisms in various economic settings.